Revision of Brazilian species of Aleochara Gravenhorst of the subgenus Xenochara Mulsant & Rey (Coleoptera: Staphylinidae: Aleocharinae) - Buss, Bruna Caroline; Caron, Edilson (Zootaxa, 2023)
Aleochara species occur in fly-infested habitats. The larvae feed on the pupae of cyclorraphous Diptera. In Brazil, four subgenera and approximately 30 species have been found. This study provides a taxonomic revision of the Brazilian species of the subgenus Xenochara. Eight species are recognized: A. (X.) puberula Klug, 1833, A. (X.) verberans Erichson, 1839, A. (X.) simulatrix Sharp, 1883, A. (X.) taeniata Erichson, 1839, A. (X.) capitinigra sp. nov., A. (X.) repetita Sharp, 1887, A. (X.) lapidicola (Sahlberg, 1844) and A. (X.) leivasorum sp. nov. One species is revalidated: A. (X.) lapicola, a former junior synonym of A. (X.) taeniata. Two synonyms are proposed: A. opacula Bernhauer, 1901 as a junior synonym of A. (X.) repetita, and A. festiva Pace, 1990 as a junior synonym of A. (X.) lapidicola. Finally, a species key and a checklist with all synonyms are provided for the Brazilian species of Aleochara (Xenochara).